TOPONIMI RUPABUMI DI KABUPATEN LANGKAT - Sahril Nfn; Yulia Fitra; Agus Mulia (Balai Bahasa Sumatera Utara, 2019)
Standardization of topographical names has been set up through Pepres No. 112/ 2006 and Permendagri No. 39/2008. The naming, naming both themselves and the naming of topographical strongly associated with language, culture and local history. The UN requires that the naming of topographical using local languages. Langkat consists of 23 districts with 272 villages. Based on the number of villages, researchers analyzed with reference to the naming of topographical topographical naming guidelines. The important thing is set in toponymy is the standardization of the procedure of writing the name of the geographical element. By default, the name of the geographical element consists of two parts: a generic name and a specific name. Among the 272 names of villages were analyzed only 68 (25%) village right under the guidelines of the standardization of topographical. Geographic elements and specific elements, there were 83 (30.51%) villages that use generic element names relating to geographic elements. 63 (23.16%) village by the name of the specific elements related to the adjective. 29 name of the village that use specific element with a direction of the wind and others. 12 name of the village that use specific elements of a good number are writing, numbers, and letters. The use of language, found writing the name of the village that does not refer to the guidelines for the standardization of topographical, geographical element should be written as a series with generic elements.